Simultaneous catalytic elimination of nitrogen oxides and organochlorine compounds over Pd/Co catalysts (2020)
ABSTRACT: This thesis deal with the environmental problem of the toxic emissions of dioxins, furans and nitrogen oxides to the atmosphere generated during combustion processes, especially in waste incineration plants. For the depuration of such exhaust gas pollutants, bimetallic palladium and cobalt catalysts supported on protonic mordenite (Pd/Co-HMOR) and sulfated zirconia (Pd/Co-SZ) were studied. The selective catalytic reduction of NO by CH4 (CH4-SCR) simultaneously with the oxidation of ortho-Dichlorobenzene (o-DCB) in gas phase were evaluated over the temperature range between 150 and 550 °C at atmospheric pressure. The o-DCB was used as a model molecule since its great structural similarity with 2,3,7,8 tetrachlorodibenzo-p-dioxin (TCDD) which is considered the most toxic dioxin congener. The Pd/Co catalysts were characterized by several physicochemical techniques such as AAS, H2-TPR, NH3-TPD, BET, TGA, Raman spectroscopy, XPS, SEM/EDS, TEM/EDS and in-situ FTIR spectroscopy studies, in order to identify the nature of the active species responsible of their activity and stability in the simultaneous reactions. Some catalytic analysis and characterizations were performed only for Pd/Co-HMOR catalyst, since this showed the better catalytic performance in the simultaneous reactions. The catalysts were tested under several operation conditions including the presence of water vapor (6%) and oxygen (10%), since these components are unavoidably present in the gas exhaust of any combustion processes. The Pd/Co-HMOR presented a better catalytic performance than Pd/Co-SZ in terms of activity and durability, for the simultaneous reactions. The Pd/Co-HMOR showed the higher conversions at 500 ºC, 40% and 99% for NO and o-DCB, respectively, in the case of Pd/Co-SZ catalyst the higher conversion of NO and o-DCB were 25% and 99%, respectively at 550 ºC. Both catalysts were highly stable for the o-DCB oxidation, however in the case of CH4-SCR, the Pd/Co-SZ almost completely deactivated after only 7 hours of continuous operation while the Pd/Co-HMOR catalyst showed a better stability performance although the NO conversion decayed by 50% after 23 h of continuous operation. The main cause of catalyst deactivation identified for Pd/Co-SZ catalyst was the loss of the sulfate group leading to the formation of the monoclinic phase of zirconia, while in the case of Pd/Co-HMOR catalyst the formation of PdO clusters explains the loss of the activity towards the CH4-SCR of NOx reaction. The in-situ FTIR study of the Pd/Co-HMOR and the comparison between the reaction rate measurements of single and simultaneous reactions showed that Co2+ Lewis sites and Brønsted acid sites are common active sites for both reactions, but there is a competition for these active sites during simultaneous reactions. Pd/Co-HMOR catalyst has a potential use in the selective catalytic reduction of nitrogen oxides by methane simultaneously with the catalytic oxidation of o-DCB under wet and lean conditions. From a technical point of view, these results open a new research field on this topic due to the possibility of the replacement of conventional NH3-SCR of NOx over vanadium-tungsten which present some risks related with the use of ammonia. The use of methane instead of ammonia as NOx reductant is a desired alternative, since the methane is widely available, easy of handle and relatively cheap.